La vulneración del derecho de motivación en dos instancias dentro de la acción de protección y la acción extraordinaria de protección como respuesta a la violación de los derechos constitucionales. - Carrillo Vizcaíno, Edison Javier (2021)
The right to motivation constitutes one of the most important constitutional rights today, because it allows the establishment of clear and precise limits between state public power and respect for the fundamental rights of people, so that it does not excesses of power are committed in the actions of the authorities, whatever their nature. However, it can show that motivation is one of the rights that are most affected within the resolutions issued by judicial and non-judicial public authorities, a fact that is particularly serious, in cases in which this right to in several instances within the same procedure, since within the various judgments of extraordinary protection actions there are cases in which various administrative authorities have breached their duty to state reasons, which leads to the filing of protection actions due to the violation of this law, which also resolve these causes with a new impact on the right to motivation, a situation that is reiterated in the appeal of these guarantees, which is why, it must be the Constitutional Court through the resolution of the extraordinary protection actions raised , which finally accounts for the violation of this right and protects it eject effectively. This situation reflects various legal problems that need to be analyzed, since in a constitutionalized State, whose priority duty is the effective protection of rights, it is inconceivable that this right is affected on multiple occasions.